Sex-based differences in patients with locally advanced pharyngeal and laryngeal SCC treated with definitive or adjuvant radiotherapy - Agolli, Linda; Reinhard, Luise; Gawish, Ahmed; Langer, Christine; Arens, Christoph; Krombach, Gabriele A.; Harth, Sebastian; Wendrich, Leon; Exeli, Ann-Katrin; Gattenlöhner, Stefan; Adeberg, Sebastian; Habermehl, Daniel; et al. (My University, 2025)
Aim: To evaluate sex-based differences in survival outcomes, toxicity, and patterns of local recurrence in patients with locally advanced head and neck squamous cell carcinoma (HNSCC) treated with definitive or adjuvant radiotherapy (RT). Methods: We conducted a retrospective review of 309 patients (246 males, 63 females) diagnosed with primary squamous cell carcinoma of the oropharynx, larynx, or hypopharynx treated with curative-intent RT at our institution between 2016 and 2023. Inclusion criteria comprised histologically confirmed SCC, stage T3/T4 and/or node-positive disease, and complete RT treatment with adequate follow-up. Survival endpoints—overall survival (OS), progressionfree survival (PFS), and metastasis-free survival (MFS)—were analyzed using the Kaplan-Meier method and log-rank tests. Patterns of local failure were classified using an established five-type system: A (central high-dose), B (peripheral high-dose), C (central intermediate- or low-dose), D (peripheral intermediate- or low-dose), and E (extraneous dose). Treatment-related toxicity was also compared between sexes. Results: No significant differences in OS, PFS, or MFS were found between male and female patients across all treatment subgroups. Log rank test did not identify any significant prognostic factor for survival and local recurrence. However, female patients experienced a higher rate of grade ≥ 3 dermatitis (12.7% vs. 5.3%, p = 0.037). Pattern A nodal failures (central high-dose volume) were significantly more common in females (64.3%) than in males (28.8%; p = 0.014), while other recurrence patterns showed no significant sex-based differences. Conclusion: Sex was not an independent predictor of survival in this cohort of locally advanced HNSCC patients. Nevertheless, the higher rate of severe skin toxicity and nodal failures in females highlights a potential need for sexadapted radiotherapy strategies and further prospective investigation.
Keywords: ddc:610